Pengendalian Internal dan Kualitas Pelayanan Disektor Kesehatan Masyarakat Pemerintah Daerah Kabupaten Garut - Nunik Lestari Dewi; I Nyoman Agus Wijaya; Gabriella Alodia Jovita (LPPM Universitas Ekasakti Padang, 2023)
One important element in achieving quality of life for national development is public health. This research is to examine the effect of internal control on the quality of health services at Garut Regency Regional Government General Hospital and Community Health Centers. The population of RSUs and community health centers in Garut Regency is 72. The sampling technique was carried out using a convenience sampling technique at 20 health facilities, consisting of 4 RSUs and 16 community health centers. Data collection was carried out using a questionnaire. The data were processed using SPSS tools and analyzed using regression tests. The results show that internal control has a 69.2% influence on the quality of health services in community health centers and hospitals in the Garut Regency Government.